Canına kıymak – 'crushing life energy': a qualitative study on lay and professional understandings of suicide and help-seeking among Turkish migrants in the UK and in the Netherlands. Issue 2 (2nd April 2016) - Eylem, O.; van Bergen, D. D.; Rathod, S.; van Straten, A.; Bhui, K.; Kerkhof, A. J. F. M.
ABSTRACT: Currently, little is known about the views that Turkish migrants hold towards suicide, which may differ from the narratives held by native inhabitants of their host countries. Central to improving the provision of mental health services, furthering our knowledge of these views is important. The aim of this research was to explore Turkish cultural understandings on suicide and help-seeking for suicide. A qualitative study included data from 6 focus groups and 7 individual interviews with 38 Turkish-speaking lay people and 4 key informants living in the Netherlands or the UK during the year 2014/2015. Through the analysis of participants' stories and narratives, the following key themes emerged in relation to suicide: suicide as an escape from failure and as a failure in itself; acculturation orientation; parenting style; and shame and stigma. There were more similarities than differences between the themes among laypersons and key informants from two countries. Canına kıymak (crushing life energy) was a strong metaphor for personal distress. Suicide was perceived as a failing of responsibilities towards the family and community. Future research should aim to give voice to all ethnocultural groups to further the present understanding of suicide and help-seeking processes in these communities.